Reading rawls: critical studies of a theory of justice - Daniels, Norman (ed.) (Oxford, 1975)
This is a collection of fourteen essays on John Rawls" A Theory of Justice, one of the most widely read and widely acclaimed works of American philosophy in re cent years. The articles, by philosophers and social scientists from both sides of the Atlantic, include material specially prepared for the collection, revisions of previously published material and several reprints of recent articles.
Keywords: "Jurisprudence Justice ,administration of........"